Morphological diversity and taxonomic delimitation of Smilax species (Smilacaceae) by multivariate analysis with an identification key for species from Northeast India - Alam, Md Sayeedul; Gargi; Vijay; Deb, Sohini; Choudhury, Hiranjit (Phytotaxa, 2025)
We investigate morphological diversity of Smilax specie from Northeast India, exploring variation in vegetative and floral characters and identifying key morphological features distinguishing each species. Using morphological traits, multivariate analysis was performed on 115 Smilax species. The findings revealed significant morphological variation among species, and two major clusters were identified by the unweighted paired group method using arithmetic mean (UPGMA). Principal component analysis (PCA) generated a 2D PCA plot. PCA supported the UPGMA clustering. A key to 29 Smilax species of Northeast India will help in proper identification.